2021
DOI: 10.21157/j.ked.hewan.v15i1.18204
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli CONTAMINATION AND ITS RESISTANCE TO ANTIBIOTICS IN SE’I MEAT

Abstract: The purpose of this study was to obtain Escherichia coli isolates from 11 se’i meat sellers in Kupang City and to observe their resistance to13 types of antibiotics. Escherichia coli were isolated and identified based on SNI 2897: 2008. Antibiotic resistance of the Escherichia colii isolates was determined using the Kirby-Bauer method. The results showed that 13 isolates (39.39%) of Escherichia coli in se’i meat samples had a high level of resistance to erythromycin (100%), tetracycline (76.92%), and doxycycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…MDR properties were found in 76 percent of E. coli isolates, with 31.1 percent resistant to 4 antibiotic classes and 2.9 percent resistant to 7 antibiotic classes. According to [30], E.coli isolated from Se'i meat in Kupang showed resistance to two or more classes of antibiotics, with 11 different resistance patterns, with the highest MDR pattern observed against nine classes of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…MDR properties were found in 76 percent of E. coli isolates, with 31.1 percent resistant to 4 antibiotic classes and 2.9 percent resistant to 7 antibiotic classes. According to [30], E.coli isolated from Se'i meat in Kupang showed resistance to two or more classes of antibiotics, with 11 different resistance patterns, with the highest MDR pattern observed against nine classes of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of antibiotic-resistant E. coli in pigs poses a significant risk, as it can lead to the contamination of pork [ 66 ] and processed meat products [ 71 ], as well as aquatic [ 27 ] and terrestrial environments [ 72 ] through improper handling of waste generated. Based on the field survey, most pig farms in Banten province were close to community settlements, and the generated waste was not handled properly.…”
Section: Discussionmentioning
confidence: 99%
“…The previous research reported that pork is a source of E. coli that produces the Shiga toxin [78]. Another study reported that the total E. coli in traditional smoked meat (beef Se'i and pork Se'i) exceeded the maximum limit required [79].…”
Section: Microbiological Characteristicsmentioning
confidence: 99%